EFFECTIVENESS OF AL-THARIQAH AL-INTIQAIYYAH IN IMPROVING ARABIC LEARNING OUTCOMES FOR ISLAMIC SENIOR HIGH SCHOOL STUDENTS - Janah, Miftachul; Nashoih, Afif Kholisun (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2019)
This study aims to determine the effectiveness of learning Arabic in improving learning outcomes by using Al-Thariqah Al-Intiqaiyyah in tenth class of science major at Islamic Senior High School 3 Jombang. This study used a quasi-experimental method with a non-equivalent control group pre-test post-test design. The population in this study were all tenth classes of science major at Islamic Senior High School 3 Jombang while the sample was tenth class of science major 8 as a control class and tenth class of science major 6 as an experimental class. Data were analyzed descriptively and inferentially.  From the test data, it can be seen that the average outcomes of the experimental class and the control class has increased. The average pre-test score of the control class was 55.25 and the average post-test score was 79.25 while the average pre-test score of the experimental class was 55.25 and the average post-test score was 87. Based on the results of the SPSS 16.0 analysis, sig values were obtained. (2-tailed) of the experimental class and the control class post-test was 0.00 which means less than 0.05. So it can be concluded that H1 is accepted then there is a significant difference between the experimental class post-test and the control class post-test. H1 acceptance proves that Al-Thariqah Al-Intiqaiyyah was effective in improving Arabic learning outcomes in tenth class of science major at Islamic Senior High School 3 Jombang.